2019
DOI: 10.1093/ageing/afz049
|View full text |Cite
|
Sign up to set email alerts
|

The effect of intravenous iron on erythropoiesis in older people with hip fracture

Abstract: Background anaemia following hip fracture is common and associated with worse outcomes. Intravenous iron is a potential non-transfusion treatment for this anaemia and has been found to reduce transfusion rates in previous observational studies. There is good evidence for its use in elective surgical populations. Objective to examine the impact of intravenous iron on erythropoiesis following hip fracture. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
47
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(49 citation statements)
references
References 16 publications
1
47
0
1
Order By: Relevance
“…Thus, the patients who had hemoglobin measured between 14 to 30 days after surgery are probably not representative of the exact hemoglobin in this postoperative period of all the patients in our study. Nevertheless, when comparing our results with other studies we acknowledge that the results on whether perioperative IV iron signi cantly recovers the hgb postoperatively are con icting (24,28,29,(42)(43)(44)(45) (29). Additionally, we acknowledge that the hemoglobin recovery especially depends on when the hemoglobin is measured postoperatively as studies have shown that IV Monofer requires several weeks before the physiological effect on the hemoglobin level is measurable (24,44).…”
Section: Discussionmentioning
confidence: 52%
See 1 more Smart Citation
“…Thus, the patients who had hemoglobin measured between 14 to 30 days after surgery are probably not representative of the exact hemoglobin in this postoperative period of all the patients in our study. Nevertheless, when comparing our results with other studies we acknowledge that the results on whether perioperative IV iron signi cantly recovers the hgb postoperatively are con icting (24,28,29,(42)(43)(44)(45) (29). Additionally, we acknowledge that the hemoglobin recovery especially depends on when the hemoglobin is measured postoperatively as studies have shown that IV Monofer requires several weeks before the physiological effect on the hemoglobin level is measurable (24,44).…”
Section: Discussionmentioning
confidence: 52%
“…Contrarily, Moppett et al have found no bene t of three daily doses of IV iron on the hemoglobin recovery seven day postoperatively among older patients undergoing hip fracture surgery (29,30).…”
Section: Introductionmentioning
confidence: 99%
“…Moppett et al tracked cardiovascular complications, infectious complications, and 30-day mortality and found no significant differences between groups. 39 In absolute terms, IV iron receiving patients experienced a similar percentage of cardiovascular complications (9% vs 10%), reduced infectious complications (21% vs 29%), and increased 30-day mortality (10% vs 0%). Serrano-Trenas et al measured 30-day mortality, infection rates, and serious adverse events.…”
Section: Resultsmentioning
confidence: 86%
“…Moppett et al measured daily Hb from admission until 7 days after surgery. 39 They found no significant difference in Hb at any point during the study. The mean admission Hb was slightly lower in the IV iron sucrose arm at 12.24 versus 12.54 g/dL in the control arm patients.…”
Section: Association Of Iron Therapy and Hb Levelsmentioning
confidence: 86%
See 1 more Smart Citation